Employees’ perception on quality work life and job satisfaction in a Private Higher Learning Institution - Saad, Hanita Sarah; Abu Samah, Ainon Jauhariah; Juhdi, Nurita (World Business Institutes, 2008)
The aim of this study is to find out about the employee’s perception of their work-life quality in the university. Previous studies indicated that employees’ perception on work life quality significantly influenced their job satisfaction. 251 employees in the university participated in this study. Ten variables to measure Quality Work Life (QWL) are examined namely support from organization, work-family conflict, relationship with peers, self competence, impact on job, meaningfulness of job, optimism on organizational change, autonomy, access to resources and time control. All these variables are tested the relationship with job satisfaction. The test indicated that each of the QWL variables on its own is a salient predictor of Job Satisfaction. However, 7 QWL variables are no longer significant predictors for job satisfaction when all the 10 QWL variables are entered into the regression equation. Using multiple linear regressions, only 3 QWL variables (meaningfulness of job, optimism on organizational change and autonomy) are significantly related to Job Satisfaction. However, they only explained 28.8% of the variance in Job Satisfaction, F (10, 240) = 11.134, p<.05.